Synthesis and characterization of sterculia gum-zwitterionic sulfobetaine-PVP based network hydrogels for biomedical application - Ankita Kumari; Diwanshi Sharma; Vikrant Sharma; Baljit Singh (Hybrid Advances, 2025)
Recently, various attempts are being made to design functional material from bioactive polysaccharide to explore their potential for clinical applications. Herein, zwitterionic sulfobetaine and polyvinylpyrrolidone (PVP) functional material was incorporated into bioactive sterculia gum (SG) for developing material in form of network structure hydrogel for use in biomedical applications. Copolymeric films were characterized by FESEM, EDS, AFM, FTIR, 13C NMR, XRD, DSC, mechanical properties & biomedical assay. Antibiotic drug was impregnated into hydrogel to enhance their healing potential for wound. Various biomedical results assessed from biomedical assays revealed their biocompatible & antioxidant nature. Hydrogel material revealed 34.80 ± 0.15 % scavenging ability of DPPH radicals. These dressing demonstrated bioadhesive characteristics and revealed their permeable nature to H2O & O2. Hydrogel dressing demonstrated 0.63 ± 0.02 N mm−2 tensile strength for dressing; 27.58 ± 2.84 N burst strength of materials along with elastic & resilience features were also analyzed. Dressing material revealed antimicrobial property against P. aeruginosa, E.coli. & S. aureus. Diffusion mechanism of cefuroxime was non-Fickian & followed Higuchi kinetic model. In 13C NMR confirmed inclusion of PMEDSAH-PVP onto SG by revealing of peaks around 62.11 ppm on an account of CH2–CH–SO3- of PMEDSAH, and peak at 43.34 ppm is due to carbon of pyrrolidone ring of PVP indicating integration of PVP into copolymeric film. Where in FTIR presence of bands at 1290 cm−1 attributed to C–N vibration of PVP, 1144 cm−1 due to SO3− asymmetric stretching along with band 1651 cm−1 by virtue CO stretching of amide of PVP. Overall these properties revealed that drug encapsulated materials could be utilize for biomedical applications including drug delivery.